Radiocarbon Dating of Silica Sinter and Postglacial Hydrothermal Activity in the El Tatio Geyser Field. Issue 11 (8th June 2020) - Munoz‐Saez, Carolina; Manga, Michael; Hurwitz, Shaul; Slagter, Silvina; Churchill, Dakota M.; Reich, Martin; Damby, David; Morata, Diego
Abstract: The El Tatio geothermal field in the Chilean Altiplano contains hydrothermal silica sinter deposits overlaying glacial and volcanic units, providing an opportunity to constrain the timing of deglaciation and volcanic activity in an area with sparse absolute chronologies. We obtained 51 new radiocarbon ages and δ 13 C values on the organic material trapped in these sinter deposits. Based on the δ 13 C values, we exclude 29 samples for possible contamination with bacterial mats that incorporate old carbon. We infer that hydrothermal activity initiated 27 ka ago and has been nearly continuous ever since. The ages of the oldest sinter deposits coincide with ages of moraines that stabilized after the most recent deglaciation. Whereas late Pleistocene sinters are broadly distributed in the field, Holocene deposits are found around active hydrothermal features. Although recent volcanism is absent in the vicinity of El Tatio, persistent hydrothermal discharge implies a long‐lived magmatic heat source. Plain Language Summary: The El Tatio geothermal field in the Chilean Altiplano contains large deposits of silica precipitated by hot springs, called sinter or geyserite. Silica sinter traps organic material that is suitable for radiocarbon dating; however, previous attempts using this methodology have shown inconsistencies that still need to be critically assessed. Here, we found that bacteria can contaminate the radiocarbon measurements leading to older radiocarbon ages. Stable carbon isotopes ( 13 C and 12 C) in dated material can be used to evaluate when the organic matter is contaminated and thus provides an unreliable age. Sinter deposits in El Tatio overlay glacial deposits and volcanic units; thus, sinter ages provide a bound for volcanism and deglaciation in the area. Uncontaminated radiocarbon ages indicate that El Tatio is a long‐lived geothermal system that started at least 27 ka ago and has been active since. However, the spatial distribution of thermal water discharge in the field has changed over time. The onset of hydrothermal activity is consistent with the onset of deglaciation in the Chilean Altiplano. Even though recent volcanic deposits are absent in the vicinity of El Tatio, the persistent discharge of hot water implies a significant long‐lived magmatic source providing heat to the geothermal system. Key Points: El Tatio is a long‐lived hydrothermal system, active for at least 27 ka Dated sinter deposits provide bounds on recent volcanic activity and deglaciation in the vicinity of El Tatio Bacterial mats trapped in sinter lead to old apparent radiocarbon ages